Mosaic Turner Syndrome Presenting with a 46,XY Karyotype - Melody Rasouli; Katherine McDaniel; Michael Awadalla; Karine Chung (Hindawi Limited, 2019)
Although Turner syndrome is most commonly associated with a 45,X genotype, other mosaic genotypes are present in approximately half of all cases. We describe a case of Turner syndrome with a 46,XY genotype by conventional 5-cell karyotype who was subsequently found to have a mosaic genotype of 18% 45,X and 82% 46,XY by 50-cell FISH analysis. Individuals with a mosaic 45,X/46,XY genotype have a variety of phenotypic presentations ranging from male to female which are not correlated with the percentage of mosaicism. Our case represents an extreme example where the genotype is predominately 46,XY and the phenotype typical of Turner syndrome.